The Executive Secretary In The Disruptive Industrial Revolution 4.0: A Comparative Analysis By Industry And Academe - Mambo, Lenda (SEIKO : Journal of Management & Business, 2023)
The objective of the study is to find out the gap between professional’s perception and the academe to square up the secretarial curriculum and classroom learning as well as the roles of lecturers in nurturing students’ competencies to cope with the requirement of the industrial revolution 4.0. The study concluded that all three components of secretary competency are important, and found that the professionals’ rating is higher than the academe in all competency components with difference of 0.24 for attitude and skill, and 0.17 for knowledge. At the critical value of t= -3.32 < -2.02, the study concludes that there is a significant difference between the professional and the academe perception. The respondents’ opinion is divided in two in their perception of components of attitude, half components are rated higher by professionals with difference of 0.09-0.30 are Social Orientation, Initiative, Analytical Thinking, Innovation, Leadership, Achievement/ Effort, Independence, Persistence, and another half are rated higher by the academe with the difference of 0.06-0.70 are Attention to Detail, Concern for Others, Self-control, Adaptability/Flexibility, Dependability, Integrity, Stress Tolerance, Cooperation. Both professionals and academe perceived skill-based form of secretarial training are important skill. All component of skills were rating higher by the professional except Service orientation which is rated higher by the academe with d=0.05. All knowledge components are considered important by the respondents except for Mathematics rated as fairly important. Four knowledge components rated higher > 0.30 by professionals are English (d=0.51), Computer application and Business administration (d=31) and Clerical administrative procedure (d=0.30). Keywords: executive secretary, secretary competency, professional assistant, secretary education